Monopsony in the U.S. labor market - Chen Yeh; Claudia Macaluso; Brad Hershbein (W.E. Upjohn Institute for Employment Research, 2022)
This paper quantifies the extent to which the U.S. manufacturing labor market is characterized by employer market power and how such market power has changed over time. We find that the vast majority of U.S. manufacturing plants operate in a monopsonistic environment and, at least since the early 2000s, the labor market in U.S. manufacturing has become more monopsonistic. To reach this conclusion, we exploit rich administrative data for U.S. manufacturers and estimate plant-level markdowns-the ratio between a plant's marginal revenue product of labor and its wage. In a competitive labor market, markdowns would be equal to unity. Instead, we find substantial deviations from perfect competition, as markdowns average 1.53. This result implies that a worker employed at the average manufacturing plant earns 65 cents on each dollar generated on the margin. To investigate long-term trends in employer market power, we propose a novel measure for the aggregate markdown that is consistent with aggregate wedges and also incorporates the local nature of labor markets. We find that the aggregate markdown decreased between the late 1970s and the early 2000s, but has been sharply increasing since.
Keywords: E2; J2; J3; J42; 330; Monopsony; labor market power; markdowns; secular trends